1999
DOI: 10.1021/bi990452s
|View full text |Cite
|
Sign up to set email alerts
|

Electron Transfer Kinetics in Purified Reaction Centers from the Green Sulfur Bacterium Chlorobium tepidum Studied by Multiple-Flash Excitation

Abstract: Reaction center preparations from the green sulfur bacterium Chlorobium tepidum, which contain monoheme cytochrome c, were studied by flash-absorption spectroscopy in the near-UV, visible, and near-infrared regions. The decay kinetics of the photooxidized primary donor P840(+), together with the amount of photooxidized cytochrome c, were analyzed along a series of four flashes spaced by 1 ms: 95% of the P840(+) was reduced by cytochrome c with a t(1/2) of approximately 65 micros after the first flash, 80% with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 42 publications
4
32
1
Order By: Relevance
“…After signal accumulation over several laser shots at a fixed magnetic field, the field was shifted and signal acquisition was repeated in order to construct the EPR spectrum of the transient P 700 ϩ A 1 Ϫ state. Flash Absorption Spectroscopy-Flash-induced absorption changes on a nanosecond time scale were measured as described previously (34), except that a laser diode emitting at 820 nm (SDL-5411-G1 from Spectra Diode Laboratories) was used as measuring light source. Excitation flashes at 532 nm were provided by a neodymium/yttrium-aluminumgarnet laser from Quantel (pulse duration, 300 ps; pulse energy, ϳ200 J/cm 2 ; repetition rate, 1 Hz).…”
Section: Methodsmentioning
confidence: 99%
“…After signal accumulation over several laser shots at a fixed magnetic field, the field was shifted and signal acquisition was repeated in order to construct the EPR spectrum of the transient P 700 ϩ A 1 Ϫ state. Flash Absorption Spectroscopy-Flash-induced absorption changes on a nanosecond time scale were measured as described previously (34), except that a laser diode emitting at 820 nm (SDL-5411-G1 from Spectra Diode Laboratories) was used as measuring light source. Excitation flashes at 532 nm were provided by a neodymium/yttrium-aluminumgarnet laser from Quantel (pulse duration, 300 ps; pulse energy, ϳ200 J/cm 2 ; repetition rate, 1 Hz).…”
Section: Methodsmentioning
confidence: 99%
“…The upshift of 29 cm -1 from the 1984 cm -1 peak is indicative of a larger degree of charge localization on one side. The isolated RC complex includes two copies of the Cytc protein (Kusumoto et al 1999;Oh-oka et al 1995).…”
Section: P840 In Green Sulfur Bacteriamentioning
confidence: 99%
“…However, the essential role of MQ as A 1 has been challenged, because preparations completely devoid of MQ but capable of electron transfer to the FeS centers were obtained (Oh-oka et al 1993;Frankenberg et al 1996;Hager-Braun et al 1997;Permentier et al 2000). Further, Kusumoto et al (1999) found no evidence that MQ acts as A 1 in their RC, although one MQ molecule remained per RC. Thus the question as to the existence of quinone and the function as an electron acceptor between A 0 and F x in the RC of green sulfur bacteria has not been settled.…”
Section: Green Sulfur Bacteriamentioning
confidence: 86%